CONNECTIVE LEARNING PEDAGOGY ENHANCES STUDENTS’ ACADEMIC PERFORMANCES BY INFUSING CRITICAL THINKING AND PROBLEM-SOLVING SKILLS - Sen, Shukdeb; Sen, Sulakshana (European Scientific Journal, ESJ, 2015)
This study is a descriptive analysis of a Connective Learning teaching technique that is based on visual intelligence infused with critical thinking skills. This technique helped students achieve higher performance in biology. Students scored 1.7 times higher grades than students who did not receive this supplemented instruction. Furthermore, students show enhanced retention and transfer of knowledge in their respective field of studies.